Evolution of the Stabilis® Database: Creation of a Level of Evidence for Stability Studies - D'Huart Elise; Lider Pauline; Vigneron Jean; Demoré Béatrice (De Gruyter, 2018)
Stabilis® is an international database on stability and compatibility of drugs. The stability data comes mainly from publications of pharmaceutical journals. As the quality of the published stability studies is not equivalent, the objective of this work was to propose a level of evidence for the physico-chemical stability studies selected for the database.